Residential Stability and Trust in the Police: an Understudied Area of Police Attitudinal Research - Lee, Heeuk Dennis (American journal of criminal justice, 2020)
Residential in/stability has been observed to influence several behavioral outcomes such as mental health, child abuse, adolescent substance uses and crime/delinquency. Despite its record of predicting behavior, residential stability has barely been explored to explain citizens’ behavior and attitudes toward their local police departments. This lack deeply affects the extent to which we can formulate policies to strengthen police and community relationship. The purpose of the present study was to explore the predictive effects of three dimensions of residential stability on residents’ perception of police trustworthiness after accounting for the effects of individual, attitudinal, and contact variables. Using community survey data collected from several areas of Northwestern states, results from the analysis found statistically significant effects for years in the community, residence, level of education, political ideology, quality and frequency of contact on residents’ assessments of police trustworthy. The implications of these results are discussed.